2022
DOI: 10.1155/2022/5186210
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Effect of the Guizhi Shaoyao Zhimu Decoction in the Treatment of Hyperuricemia

Abstract: Traditional Chinese Medicine (TCM) is a medical system with a distinctive theoretical framework and extensive experience in identification and treatment acquired by the Chinese people in long-term medical practice and life practice. It is a complete, integrated, and complex knowledge system in epistemology. This study is aimed at exploring the clinical effectiveness of TCM called the Guizhi Shaoyao Zhimu Decoction in the treatment of hyperuricemia. A total of 100 patients with hyperuricemia at the Medical Coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Therefore, an antiinflammatory effect is produced. Furthermore, GSZD can lower serum uric acid levels [141,142]. the positive drug [143].…”
Section: Tcm Prescription For Goutmentioning
confidence: 99%
“…Therefore, an antiinflammatory effect is produced. Furthermore, GSZD can lower serum uric acid levels [141,142]. the positive drug [143].…”
Section: Tcm Prescription For Goutmentioning
confidence: 99%
“…The common deficiency syndrome in clinical practice is the deficiency cold syndrome of the middle viscera, but there is also abdominal pain of spleen yin deficiency syndrome, which cannot be ignored. Chen Ying [21] in the clinical treatment of patients with spleen yin deficiency syndrome, has a good effect. The patient had abdominal pain deficiency syndrome, but other symptoms showed that it was not Taiyin deficiency syndrome or Yangming disease.…”
Section: Application In Abdominal Painmentioning
confidence: 99%
“…Shi Wei Ru Xiang ameliorates renal dysfunction in mice with hyperuricemia (Li et al, 2022). Similarly, Jianpishenshi (Yin et al, 2022), Jiangniaosuan (Guo et al, 2022), Gegen Qinlian decoction (Wang et al, 2021), Guizhi Shaoyao Zhimu decoction, and so forth are also recently reported as potential therapeutic drugs for hyperuricemia (Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%